2014
DOI: 10.1021/bm401652c
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of 1-Ethyl-3-methyl-imidazolium Acetate in Glucose, Cellobiose, and Cellulose Solutions

Abstract: Solutions of glucose, cellobiose and microcrystalline cellulose in the ionic liquid 1-ethyl-3-methyl-imidazolium ([C2mim][OAc]) have been examined using pulsed-field gradient 1H NMR. Diffusion coefficients of the cation and anion across the temperature range 20–70 °C have been determined for a range of concentrations (0–15% w/w) of each carbohydrate in [C2mim][OAc]. These systems behave as an “ideal mixture” of free ions and ions that are associated with the carbohydrate molecules. The molar ratio of carbohydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 35 publications
6
59
0
Order By: Relevance
“…ions to cellulose was also proposed from SAXS experiments (Behrens et al 2016). The obtained result can be compared with previous work on glucose, cellobiose and MCC dissolved in 1-ethyl-3-methyl-Imidazolium acetate, where the diffusion of both the cation and the anion species were monitored (Ries et al 2014). Ries et al demonstrated that the cations were preferentially solvating the glucose units/molecule and a value of three associated ions per AGU was estimated for the cellulose.…”
Section: Resultsmentioning
confidence: 65%
“…ions to cellulose was also proposed from SAXS experiments (Behrens et al 2016). The obtained result can be compared with previous work on glucose, cellobiose and MCC dissolved in 1-ethyl-3-methyl-Imidazolium acetate, where the diffusion of both the cation and the anion species were monitored (Ries et al 2014). Ries et al demonstrated that the cations were preferentially solvating the glucose units/molecule and a value of three associated ions per AGU was estimated for the cellulose.…”
Section: Resultsmentioning
confidence: 65%
“…The calculated MSD for EMIM OAc compares well with available experimental values, and reproduces the experimentally observed difference between the cation and anion diffusion coefficients (i.e., the anion diffuses B0.9 times that of the cation). 47 The solvation of IL-cellulose systems at the molecular level has been characterized via radial distribution functions (RDFs), conformation of the o dihedral (i.e., trans-gauche, gauche-trans and gauche-gauche) and the j-c plots for the glycosidic bond. 23,25,50 The following sections discuss and compare each of these characteristics, in detail, from the context of EMIM OAc, BMIM OAc and OMIM OAc solvation of glucose and cellobiose with respect to an aqueous environment.…”
Section: Resultsmentioning
confidence: 99%
“…19,24,46 Here, this is not the case as peaks 1 and 3 move the most and do so in an upfield sense. At low mole fraction of DMSO (<0.4), peak 2 has instead a downfield movement, and Δδ is greater than that of the anion.…”
Section: Whereas In [Emim][oac]−dmso It Has Onlymentioning
confidence: 96%
“…41,46,52,53 Figure 9 shows NMR Relaxometry−Viscosity Analysis. Next, we correlate spin−lattice relaxation time T 1 with macroscopic viscosity.…”
Section: In the [Emim]mentioning
confidence: 99%